FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGEMBALIAN BANTUAN LANGSUNG MASYARAKAT PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN (BLM – PUAP) DI KABUPATEN ACEH SINGKIL - Hendra Sunarno; Rahmanta Ginting; Erwin Pane (Universitas Medan Area, 2018)
Community Facilities Direct Assistance Program Rural Agribusiness Development ( BLM - PUAP ) is part of an effort to empower the farming community , which is followed by a related activity, namely institutional strengthening farmers and growers of human resource development through coaching, counseling , training , monitoring and evaluation . Directorate General of Horticulture ( 2010) states that the purpose of the agricultural community empowerment through PUAP are : 1 ) strengthen the capital of entrepreneurs in developing agribusiness and food security , 2) increase the production , productivity and farm income entrepreneurs ; 3 ) develop agriculture and agro-industry in regional development ; 4 ) increase the independence and group cooperation ; 5 ) encouraging the development of microfinance institutions agribusiness and other rural economic institutions. The problem in this study is How the credit characteristics of the recipient farmers PUAP BLM programs in Aceh Singkil, what are the factors that affect the rate of return PUAP BLM program in Aceh Singkil The purpose of this study was to investigate the characteristics of the receiving farmer credit program in Aceh BLM PUAP Singkil , to analyze the factors that affect the rate of return PUAP BLM program in Aceh Singkil KabupatennThe method used in this research is the analysis of qualitative and quantitative methods . The qualitative method is done through analysis deskripktif to describe the characteristics one by one farmer in the form of tabulations are intended to support the quantitative analysis . As for analyzing the factors that affect the loan repayment rate PUAP program , used logistic regression analysis models ( binary logit ) . The data used is primary data collected from farmers' groups PUAP recipients for 2010 program in Aceh Singkil with 71 samples of 250 farmer beneficiaries PUAP in 7 districts and 7 village of 10 existing sub-district in Aceh Singkil. 71 (seventy one ) farmers are taken to be sampled , characteristics most farmers aged 35-44 years , the end of junior high school education , have a number of dependents 3-4 people , has a net income of 2-3 million , with a land area of 3000m2 - 10000m2 and loan amount ranges from 3-5 million by the number of respondents in the current loan repayments are as many as 34 respondents out of the total respondents were 71 people . Factors ¬ factors are real and significant effect on loan repayment program Rural Agribusiness Development ( PUAP ) in Aceh Singkil is : Total loans, net income, age and education. Keywords : BLM - PUAP, purposive, Gapoktan